Islamization of Economy in Pakistan (1977-88): An Essay on the Relationship between Religion and Economics (The Pakistan Development Review, 1991)
The Martial Law regime which came into power in Pakistan on July 5, 1977 after a political crisis undertook a comprehensive scheme of Islamizing the political, legal, economic and educational areas of the Pakistani society. Ordinances and Laws on Zakat (poor-due), 'Ushr (tithe), elimination of riba (interest/ usury), profit and loss scheme, mudaraba (profit-sharing), and twelve modes of Islamic finance, were promulgated with the avowed aim of transforming the Pakistani economy into an Islamic economic system. In this article we shall confine ourselves to an examination of the Islamization of the economy only; that is, the article shall focus on the relationship between religion and economics in general, and Islam and economics in particular. Since the times of Adam Smith (1720-1790), and especially after the works of Lionel Robbins (1898-1984) the modern economy is generally taken by the economists as an autonomous economic system and modern economics, an important branch of the social sciences, has gradually become independent from religion. In both capitalist and socialist versions, economics is generally defined as the "study of the social laws governing production and distribution of the material means of satisfying human needs" [Lange (1963)].